Hubungan Pengetahuan Ibu Dengan Pemanfaatan Buku KIA - Susi Rabuana; Hamdiah Anas; Iin Fadhilah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
The Maternal and Child Health (MCH) Handbook is an important medium in maternal and child health services, serving as a recording, education, and communication tool between health workers and mothers. However, the utilization of the MCH Handbook by mothers is still suboptimal. One factor influencing the utilization of the MCH Handbook is the mother's level of knowledge. This study aims to determine the relationship between maternal knowledge and the utilization of the MCH Handbook. The research method used was quantitative with an analytical design and a cross-sectional approach. The study sample consisted of mothers who owned the MCH Handbook and visited health care facilities. Data were collected using a questionnaire and analyzed using statistical tests. The results showed a significant relationship between maternal knowledge and utilization of the MCH Handbook (p < 0.05). The conclusion of this study is that the better the mother's knowledge, the more optimal the utilization of the MCH Handbook.